Upaya Meningkatkan Kemampuan Menggiring Bola Dalam Permainan Sepak Bola Dengan Modifikasi Alat - Aswandi, Beni (Universitas PGRI Pontianak, 2025)
This research aims to improve the basic technique of dribbling the ball in football games using modified equipment. This study is a Classroom Action Research (CAR) conducted in two cycles, each cycle consisting of 4 stages, namely Planning, Implementation, Observation, and Reflection with the process (1) Improving the ability to dribble the ball by applying equipment modifications. (2) Planning the form of action in cycle II based on the results of reflection on cycle I. The research subjects were 22 seventh grade students of MTs Al Huda Mubung, Hulu Gurung District, Kapuas Hulu Regency. The results of the study showed that in the first cycle 15 people (68%) of students achieved the KKTP score (75), while 7 students (31.8%) were below the KKTP score. Cycle II showed that only 2 people (9.09%) did not achieve the KKTP score, while 20 students (90.9%) achieved the KKTP score. This illustrates that learning to improve the ability to dribble the ball in soccer games with equipment modifications can be declared successful and can be applied in schools, therefore it is recommended that teachers in teaching and learning activities should use various methods to improve students' abilities, one of which is implementing equipment modifications in the subject of Physical Education, Sports and Health.